EVALUASI EFISIENSI OPERASIONAL MENGGUNAKAN BEP DAN MARGIN OF SAFETY PADA CV MANDIRI KARYA KONSULTAN - Amanda Aveline Cornelia; Zumrotul Fitriyah (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
This study aims to analyze the operational efficiency of CV Mandiri Karya Konsultan by calculating the Break Even Point (BEP), Contribution Margin (CM), and Margin of Safety (MoS) on a quarterly basis. Financial data from January to September 2025 were analyzed quantitatively and supplemented with qualitative interviews with the company owner. The results show significant performance improvement, namely in the first quarter the company experienced a loss, then in the second quarter the company reached the break-even point, and in the third quarter the company managed to achieve optimal performance with the highest Margin of Safety. This improvement was supported by a consistently high Contribution Margin ratio of above fifty-nine percent, which indicates the company's ability to manage costs and enhance profitability. This study provides practical guidance for construction service businesses in using BEP and MoS analysis as tools for evaluating operational performance. This study provides a comprehensive overview of efficiency improvements based on quarterly data and demonstrates the company's ability to strengthen its financial position through effective cost management and revenue strategies.